THE ROLE OF THE MIRROR NEURON SYSTEM IN THE ACQUISITION OF EMERGENCY MEDICINE PROCEDURAL SKILLS: A COMPREHENSIVE NARRATIVE REVIEW - Kateryna Shtohryn; Szymon Rudawski; Magdalena Zięba; Magdalena Morytko; Maja Elertowicz; Mikołaj Moskwa; Patrycja Herod; Aleksandra Wójciak (International Journal of Innovative Technologies in Social Science, 2025)
Background: Emergency medicine requires precise and rapid execution of high‑risk procedures in time-sensitive environments, leaving limited opportunities for safe supervised practice. Neuroscientific discoveries, particularly related to the mirror neuron system (MNS), suggest that observational learning may effectively enhance motor skill acquisition without risk to patients. Aim: To comprehensively review the neurobiological foundations, educational applications, and practical implications of the MNS in emergency medicine procedural training. Material and methods: Narrative review including PubMed, Scopus, Web of Science. Literature (2000–2024) concerning neuroscience, medical education, motor learning, and emergency medicine was analyzed. Results: Studies demonstrate that the MNS supports imitation, enhances procedural memory formation, and strengthens early motor skill acquisition. Educational strategies such as expert modeling, action observation, motor imagery, and multimodal simulation appear aligned with MNS activation and may optimize procedural training. Conclusions: The MNS offers a valuable, underutilized framework for optimizing procedural training in emergency medicine. Future research should integrate neurophysiological tools into educational research to directly examine the mechanisms by which observational learning enhances clinical performance.